The Landscape of Consumption Shopping Streets and Cultures in Western Europe, 1600–1900 - Furnée, Jan Hein.; Lesger, Clé.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This volume brings together research on retailing, shopping and urban space; themes that have attracted wide interest in recent decades. The authors argue that the 'modernity' of the nineteenth century is often over-emphasised at the expense of recognising earlier innovation.
Keywords: Social history; Europe-History.; Civilization-History.; History, Modern; Social History; Organizational Studies, Economic Sociology; European History; Cultural History; Sociology, general; Modern History